WORKPLACE WELL-BEING AS A CATALYST FOR ORGANIZATIONAL GROWTH: A GIG ECONOMY PERSPECTIVE - Soans, Rovina Sharon; Naik, Sheker (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The gig economy, characterized by short-term contracts and freelance work, has witnessed unprecedented growth, fundamentally reshaping traditional employment structures. This study explores the crucial role of workplace well-being as a catalyst for organizational growth within this rapidly expanding sector. Gig workers face distinct challenges, including job insecurity, fluctuating income, and the absence of traditional employment benefits, which negatively impact their mental health, job satisfaction, and overall productivity. These factors contribute to stress, burnout, and decreased work efficiency, ultimately affecting organizational performance. By implementing targeted well-being initiatives—such as flexible work arrangements, mental health support programs, financial literacy training, and access to healthcare benefits—organizations can significantly enhance the quality of life for gig workers. The study examines global best practices and Indian government policies, including insights from the NITI Aayog (2022) report on India's gig economy, highlighting the necessity of structured welfare measures. Additionally, the study explores how organizations can leverage workplace well-being as a strategic tool to attract and retain talent in the gig economy. A well-designed well-being framework not only boosts worker engagement and productivity but also strengthens organizational reputation and sustainability. This research emphasizes the need for policy reforms, corporate responsibility, and collaborative efforts between businesses and governments to create an inclusive and fair gig economy. Ultimately, integrating well-being strategies into gig work environments fosters a mutually beneficial ecosystem, ensuring long-term growth for both workers and organizations.